Curcumin induces chemo/radio-sensitization in ovarian cancer cells and curcumin nanoparticles inhibit ovarian cancer cell growth - Yallapu Murali M; Maher Diane M; Sundram Vasudha; Bell Maria C; Jaggi Meena; Chauhan Subhash C (BMC, 2010)
Abstract Background Chemo/radio-resistance is a major obstacle in treating advanced ovarian cancer. The efficacy of current treatments may be improved by increasing the sensitivity of cancer cells to chemo/radiation therapies. Curcumin is a naturally occurring compound with anti-cancer activity in multiple cancers; however, its chemo/radio-sensitizing potential is not well studied in ovarian cancer. Herein, we demonstrate the effectiveness of a curcumin pre-treatment strategy for chemo/radio-sensitizing cisplatin resistant ovarian cancer cells. To improve the efficacy and specificity of curcumin induced chemo/radio sensitization, we developed a curcumin nanoparticle formulation conjugated with a monoclonal antibody specific for cancer cells. Methods Cisplatin resistant A2780CP ovarian cancer cells were pre-treated with curcumin followed by exposure to cisplatin or radiation and the effect on cell growth was determined by MTS and colony formation assays. The effect of curcumin pre-treatment on the expression of apoptosis related proteins and β-catenin was determined by Western blotting or Flow Cytometry. A luciferase reporter assay was used to determine the effect of curcumin on β-catenin transcription activity. The poly(lactic acid-co-glycolic acid) (PLGA) nanoparticle formulation of curcumin (Nano-CUR) was developed by a modified nano-precipitation method and physico-chemical characterization was performed by transmission electron microscopy and dynamic light scattering methods. Results Curcumin pre-treatment considerably reduced the dose of cisplatin and radiation required to inhibit the growth of cisplatin resistant ovarian cancer cells. During the 6 hr pre-treatment, curcumin down regulated the expression of Bcl-XL and Mcl-1 pro-survival proteins. Curcumin pre-treatment followed by exposure to low doses of cisplatin increased apoptosis as indicated by annexin V staining and cleavage of caspase 9 and PARP. Additionally, curcumin pre-treatment lowered β-catenin expression and transcriptional activity. Nano-CUR was successfully generated and physico-chemical characterization of Nano-CUR indicated an average particle size of ~70 nm, steady and prolonged release of curcumin, antibody conjugation capability and effective inhibition of ovarian cancer cell growth. Conclusion Curcumin pre-treatment enhances chemo/radio-sensitization in A2780CP ovarian cancer cells through multiple molecular mechanisms. Therefore, curcumin pre-treatment may effectively improve ovarian cancer therapeutics. A targeted PLGA nanoparticle formulation of curcumin is feasible and may improve the in vivo therapeutic efficacy of curcumin.